2013
DOI: 10.1186/2196-1042-14-4
|View full text |Cite
|
Sign up to set email alerts
|

Occlus-o-Guide®versus Andresen activator appliance: neuromuscular evaluation

Abstract: BackgroundThe aim of the present study was to assess the muscular variations at the electromyography (EMG) level for the anterior temporalis muscles and masseter muscles during treatment with Occlus-o-Guide® and Andresen activator appliances.MethodsEighty-two patients (35 males and 47 females) aged between 8 and 12 years (mean age, 10.5 ± 0.8 years) participated in the study. Fifty patients underwent treatment with an Occlus-o-Guide® and 32 patients with an Andresen activator. All patients underwent EMG examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…[17][18][19][20][21] The analysis of results, independently from the considered arch, shows that the discrepancies reported for the virtual diagnostic protocol are, on average, lower than those obtained in the group receiving the nonvirtual diagnostic protocol. Presurgical templates allow the orthodontist to more easily achieve the objectives set in the diagnostic phase.…”
Section: Discussionmentioning
confidence: 92%
“…[17][18][19][20][21] The analysis of results, independently from the considered arch, shows that the discrepancies reported for the virtual diagnostic protocol are, on average, lower than those obtained in the group receiving the nonvirtual diagnostic protocol. Presurgical templates allow the orthodontist to more easily achieve the objectives set in the diagnostic phase.…”
Section: Discussionmentioning
confidence: 92%
“…These results have been obtained with both electromyographic systems. The following authors also proved that high-angle cases were associated with weaker musculature than low-angle patients: Moller [ 25 ], Sassouni [ 47 ], Ingervall and Thilander [ 26 ], Bakke and Michler [ 27 ], Kayukawa [ 28 ], Farronato et al [ 29 ], and Bong et al [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ahlgren et al [ 22 , 23 ] proved that the mandibular plane angle (SN-GoMe) was positively correlated to temporal muscle activity, while Lowe et al [ 24 ] obtained contradictory results. Moller [ 25 ], Ingervall and Thilander [ 26 ], Bakke and Michler [ 27 ], Kayukawa [ 28 ], Farronato et al [ 29 ], and Bong et al [ 30 ] demonstrated that high mandibular angle cases were associated with weaker musculature as opposed to stronger musculature in the low-angle cases. Kayukawa [ 28 ] and Farronato et al [ 29 ] showed higher masticatory muscle activities in deep bite patients than in open bite ones.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors observed that maxillary expansion has different effects in class I, II, and III malocclusions [ 3 , 17 - 22 ]. In the retrospective studies of Farronato et al on 15 growing subjects with maxillary hypoplasia, the effects of RME in the three planes of space were investigated.…”
Section: Introductionmentioning
confidence: 99%